Analisis Indikator Pariwisata Kota di Jawa Tengah: Peran Kunjungan Wisatawan, PDRB, dan Destinasi Wisata - Musahal Annaty; Jeane Talakua (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the determinants of tourism revenue in six cities across Central Java (2015-2023) using fixed-effects panel regression with robust standard errors. Results indicate that tourist visits significantly boost revenue (β=255,540.34; p=0.002), while GRDP and destination quantity show statistically insignificant effects. Spatial disparities dominate, with 76.6% of variance attributed to city-specific heterogeneity (ρ=0.766). The model explains 65.74% of within-city revenue variation (R²_within=0.6574). Policy recommendations prioritize digital promotion, infrastructure equity, and GRDP-tourism synergy. Findings challenge conventional assumptions about short-term macroeconomic impacts on regional tourism.